UTILIZING COMIC STRIPS IN ENHANCING STUDENTS’ WRITING NARRATIVE SKILL - Rila Zikria (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
Commonly, teaching writing seems difficult due to its complexity involving many aspects of language. As well as a narrative text – a true story or fiction appears to be more complex that needs a fascinating way to teach it. Therefore, the study aims at finding out whether or not using comic strips can enhance students’ writing narrative skills. To carry out this study, the writer uses IX. 2 as the subject of this study. By means of the data collected from of pre-test and post-test, the result shows that utilizing comic strips can successfully enhance students’ writing narrative skill reflected in the post-test result of their composition covering all language aspects called content, organization, vocabulary, grammar, and mechanics. The significant difference in the findings can be seen in the average score: content increased from 11.8 to 16.2, the organization from 11.8 to 15.8, vocabulary from 9.6 to13, grammar from 7.8 to 11, and mechanics from 9.4 to 12.2 with the improvement for each aspect was 4.4, 4, 3.4, 3.2, and 2.8. Based on these proofs, it can be concluded that utilizing comic strips can successfully enhance students’ writing narrative skill. Consequently, finding an attractive way in teaching narrative writing such as using comic strips is required in order to overcome students' writing difficulties.